Carbon pricing of food in Australia: an analysis of the health, environmental and public finance impacts. (8th October 2018) - Springmann, Marco; Sacks, Gary; Ananthapavan, Jaithri; Scarborough, Peter
Abstract: Objective: To estimate the impact of integrating the price of greenhouse gas emissions into the price of food commodities on dietary and weight‐related risk factors and associated disease burden in Australia, as well as on national emissions reductions and public revenues. Methods: We used country‐specific data for Australia to build a coupled modelling framework that includes economic, environmental and health analyses. Data sources included the 2011‐12 Australian food and nutrition survey, meta‐analysis of food‐related lifecycle emissions, and price and income elasticities. Consumption‐related changes in disease burden were calculated using a comparative risk assessment framework with 11 disease states and seven diet and weight‐related risk factors. Results: Including a price of $23 per tonne of carbon dioxide equivalent (tCO2‐eq) – the starting price of the former Australian carbon pricing mechanism – into the price of food commodities in our model simulations led to 49, 500 avoided disability‐adjusted life years (DALYs) (95% confidence interval [CI] 43, 200‐55, 200). Food‐related greenhouse gas emissions were reduced by 6% (2.3 MtCO2‐eq), and greenhouse gas tax revenues amounted to $866 million. Conclusion: Incorporating the price of food‐related greenhouse gas emissions into the price of food commodities in Australia could be beneficial for population health, while generating public finance revenues and supporting Australia's emission‐reduction commitment. Implications for public health: Climate policies that integrate the price of greenhouse gas emissions into the price of food commodities in Australia are compatible with public health objectives to reduce diet‐related disease mortality.